Inequality, income, and democracy in perspective: Insights from novel data analysis - Rute Martins Caeiro; Rachel M. Gisselquist; Klarizze Anne Martin Puzon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
The relationship between economic development, inequality, and democratization has long been debated in the literature. Yet empirical analyses of this interplay have been limited and have yielded overall mixed and inconsistent results. This paper seeks to address this gap by examining the impact of income inequality on democracy, focusing particularly on the influential theory proposed by Acemoglu and Robinson, which predicts an inverted U-shaped relationship between inequality and democracy. Combining democracy indicators from the V-Dem Project with inequality data from the World Income Inequality Dataset, our empirical findings indicate no discernible net effect of inequality on democracy and no support for the predicted inverted U-shaped relationship. Our results are robust across different identification strategies, outcome variable choices, and subsample analyses. We present this analysis not as decisive evidence against the theory, but rather as an indication that it requires more rigorous empirical scrutiny to justify its continued prominence in the literature.
Keywords: D72; P00; D63; 330; democracy; inequality; income